RANCANG BANGUN SISTEM INFORMASI GEOGRAFIS PEMETAAN OPTICAL DISTRIBUTION POINT (ODP) PADA PT. TELKOM AKSES BALI SELATAN BERBASIS WEB DAN ANDROID - Dewi Sintyarianti, Anak Agung; Arsa Suyadnya, I Made; Care Khrisne, Duman (Jurnal SPEKTRUM, 2018)
PT Telkom Access (PTTA) is a provider of network infrastructure construction and management services. The company is experiencing various obstacles in managing network infrastructure. One of them is the inefficient coordination between technicians and helpdesk when connecting ODP. In order for technicians to immediately connect customers with the nearest ODP, the technicians need specific ODP location information to be fixed. So far no ODP mapping system has been used. Based on the existing problems, then this research proposes the design and development of Geographic Information System Application mapping ODP web-based for helpdesk and Android mobile-based apps for technicians. Based on the results of testing the application with Black-box testing method, all the functionality of ODP mapping system on web and Android that has been built can run well.